(untitled) - Engels, Friedrich (Chicago, 1907)
The word "conversion" contains in itself the distinction between the socialism of thirty years ago and that of to-day. Men are not now individually converted to socialism but whole groups and classes are driven into the socialist ranks by the pressure of circumstances.
Keywords: Dialectical materialism,Duy vật biện chứng,Chủ nghĩa xã hội,Socialism